Stress absorbing membrane innerlayer : final report. - Hardy, Thomas A.; Brock, Leon G.; Beecroft, Gordon; Oregon State Highway Division. Research Section
The westbound lanes of the South Baker Interchange-Encina Interchange Section of I-84 were overlayed in 1977. A stress absorbing membrane innerlayer (SAMI), was included in this overlay as an experimental feature. This report is the final evaluation of the SAMI. Although the pavement did not perform as well as expected, the analysis of the SAMI's performance was complicated by two factors; lack of a control section and the deficient aggregate furnished for the overlay. The material deficiencies which had contributed to failure of the original pavement were also present in the overlay.